DC-programming for neural network optimizations - Awasthi, Pranjal; Mao, Anqi; Mohri, Mehryar; Zhong, Yutao (Journal of global optimization, 2024)
We discuss two key problems related to learning and optimization of neural networks: the computation of the adversarial attack for adversarial robustness and approximate optimization of complex functions. We show that both problems can be cast as instances of DC-programming. We give an explicit decomposition of the corresponding functions as differences of convex functions (DC) and report the results of experiments demonstrating the effectiveness of the DCA algorithm applied to these problems.